Serum elabela levels in women with tubal ectopic pregnancy: A case-control study - Gül, Evrim; Deniz, Rulin; Kavak, Ebru Celik; Şanlı, Cengiz; Batmaz, İbrahim; Bulu, Gülay; Baykus, Yakup (My University, 2020)
Elabela, a circulating peptide hormone derived from the placenta, plays a crucial role in embryonic development and function of the human placenta during pregnancy. Weaimed to investigate serum elabela levels in ectopic pregnancy. Sixty cases admitted to Emergency Department and Obstetrics and Gynecology Clinic were included in thiscase-control study. Thirty women with tubal ectopic pregnancy constituted Group 1 and 30 women with healthy pregnancy served as controls (Group 2). Blood sampleswere collected from all participants. Demographic and obstetric characteristics of the whole study cohort were also recorded. Levels of serum elabela were measured ineach group by enzyme-linked immunosorbent assay . Age, gender, gestational age, obstetrics history, and body mass index of the groups were similar. Mean serum elabelalevels were 7.52 ± 1.1 ng/mL and 7.05 ± 1.2 ng/mL in group 1 and group 2, respectively. There was no statistically significant difference between the two groups with respectto serum elabela levels (t=1.581, p=0.119). In the present study, serum elabela levels were not significantly different in women with ectopic pregnancies than healthypregnancies. Since placenta is the primary source of elabela, this lack of difference might be due to the insufficient placental as well as fetal development in fallopian tubes.
Keywords: Kadın Hastalıkları ve Doğum; Patoloji